Surficial sediment texture from the Iberian Atlantic Margin Sediments Database (IBAM-Sed) - Susana Costas; Margarida Ramires; Isabel Maria de Paiva Pinto Mendes; Óscar Ferreira (PANGAEA, 2017)
This sample collection presents a database that integrates surficial sediment samples collected and analysed for textural characterization within the frame of a series of research projects. A total of 4727 samples within the frame of 24 projects developed between 1996 and 2015 along the southern Atlantic coast of the Iberian Peninsula. The projects had different purposes, including fishing exploration, coastal dynamics investigation or monitoring of nourished beaches. The variety of the projects also explains the variety of environments that have been sampled and compiled within this database. The latter includes beaches (emerged to nearshore sediments), estuaries (bed surface sediments), lagoons (bed surface sediments from channels, inlets and inner beaches), and the adjacent continental shelf (from the nearshore area to 300 m depth). Data collection was performed by hand (at beaches and inlets) and using grab samplers (at the shelf). All collected samples were examined and analysed in order to determine their grain-size distribution. Due to the diversity of environments sampled and the subsequent variety of sediments, different methods were used to determine grain size properties. For those samples with grain sizes between sand and gravels, the distribution of size fractions was obtained through dry sieving at each 0.5 phi, except for CRIDA, EMERGE, SIRIA and SIMPATICO datasets which have been analysed at each phi. For those cases with grain sizes finer than sand (i.e. silt and clay fractions), the pipette or settling tube was used and the corresponding fractions analysed at each phi. The value *0.999 is given for "not recovered record".
Supplement to: Costas, Susana; Ramires, Margarida; de Sousa, Luisa B; Mendes, Isabel Maria de Paiva Pinto; Ferreira, Óscar (2018): Surficial sediment texture database for the south-western Iberian Atlantic margin. Earth System Science Data, 10(2), 1185-1195, https://doi.org/10.5194/essd-10-1185-2018